On-plant larval movement and feeding behavior of fall armyworm (Lepidoptera: Noctuidae) on reproductive corn stages - Pannuti, L. E. R. [UNESP]; Baldin, E. L. L. [UNESP]; Hunt, T. E.; Paula-Moraes, S. V. (Oxford University Press, 2015)
Spodoptera frugiperda J.E. Smith (fall armyworm) is considered one of the most destructive pests of corn throughout the Americas. Although this pest has been extensively studied, little is known about its larval movement and feeding behavior on reproductive compared to vegetative corn stages. Thus, we conducted studies with two corn stages (R1 and R3) and four corn plant zones (tassel, above ear, ear zone, and below ear) in the field at Concord, NE (USA), and in the field and greenhouse at Botucatu, SP (Brazil), to investigate on-plant larval movement. The effects of different corn tissues (opened tassel, closed tassel, silk, kernel, and leaf), two feeding sequence scenarios (closed tassel-leaf-silk-kernel and leaf-silk-kernel), and artificial diet (positive control) on larval survival and development were also evaluated in the laboratory. Ear zone has a strong effect on feeding choice and survival of fall armyworm larvae regardless of reproductive corn stage. Feeding site choice is made by first-instar. Corn leaves of reproductive plants were not suitable for early instar development, but silk and kernel tissues had a positive effect on survival and development of fall armyworm larvae on reproductive stage corn.
Keywords: Spodoptera frugiperda; Feeding behavior; Larval dispersal; Larval movement